Ефикасност на фракционен ласер во обновувањето на кожата - Петров, Андреј (Медицински факултет, УКИМ, Скопје, 2015)
Introduction: Fractional carbon dioxide laser is used in the treatment of many dermatological diseases, as well as in several aesthetic procedures. Main objectives: of the study are: to confirm the efficiency and safety of the fractional CO2 laser in skin renewal, and to check the possibility of having a synergistic effect in patients who besides carbon dioxide laser are treated with PRP /platelet-rich plasma/ too. Material and methodology: The study was prospective,case control study and was carried out at AcibademSistina Clinical Hospital, at the Department of Dermatovenerology, in the period from 2013 - 2015, with total number of 232 patients included in the study. The patients were divided into three groups.The first group (Examined Group 1) included 107 patients treated with fractional CO2 laser (Lutronic eCO2) as month therapy. The second group /Control Group/ covered 100 patients treated with neither laser nor plasma in the same period but subjected to local therapy with drugs or other physio-procedures under the existing protocols for treatment of certain diseases. The third group /Examined Group 2/ treated 25 patients with combined therapy of CO2 laser and PRP in the treatment of facial rejuvenation or treatment of acne scars. Inclusive criteria for entering the study are patients who have one of the following clinical conditions: acne and residual efflorescence of acnes, scars from different backgrounds, stretches, photodamaged skin, hyperpigmentation, xantelasma, syringoma, viral warts. Exclusionary criterion in the study is the use of: oral retinoids in period of 6 months prior to the laser treatment, use of anticoagulation therapy, age under 18, presence of systemic diseases in the patient, using artificial light sources, sauna, during the treatment, use of fillers,, pregnancy and herpes viral skin infections/HPV. The laser interventions are performed with different pulse energy, strength, density and number of passes in a single session, and also with a different number of sessions, depending on the protocols of a particular disease (acne scars require a minimum of three sessions; skin rejuvenation 3-4 sessions, viral warts 1-2 sessions of laser treatment). Patients in the second group (CG) undergone therapeutic modalities depending on the diagnosis of the disease, and according to the existing protocols for certain diseases. There was one of the three elective standard therapeutic non-laser treatments to compare, widely used in everyday ambulatory practice. For patients with acne scars and patients who undergone rejuvenation, the comparison was made with retinoids, topically applied to the skin. For patients with viral diseases/HPV/ of the skin, comparison was made with standard, the most widely used method for treatment of these diseases – cryotherapy. In the treatment of the third group of patients (Examined Group 2) two methods were used: treatment with eCO2 laser and PRP. Two weeks after the last laser treatment 25 patients took two sessions of PRP injections with a dermaroler type 0.5 and 1mm, and 30G needle. Within the PRP method own platelet-rich plasma with a high growth factor is injected. It is actually a stimulation of fibroblasts and induction of a new collagen. Before starting the treatment the patient 6 ccm blood was drawn, processed and centrifuged in our hematological laboratory. The study differentiated three major subgroups of patients with statistical significance in the examined group treated with laser as monotherapy. The first subgroup are patients with acne scars, the second large subgroup are patients treated for rejuvenation of the skin. They were compared with the patients who used a topical retinoid - Adapalene in the therapy (control group of 66 patients) and with patients undergoing laser treatment combined with PRP method - Examined Group 2 (25 patients). In patients with viral/HPV/ skin growths (third subgroup of 54 patients) there was comparison between laser therapy and other therapeutic modalities under the protocols, primarily with widely used metod - cryotherapy. All treated patients were monitored for the effectiveness of laser therapy and the side effects of it. Before and after the treatment the patients were photographed and digital photographs were a basis for assessing the effect of the treatment. Each patient individually filled out informative consent and a questionnaire to assess the effects of the treatment, as well as a separate questionnaire for subjective evaluation of the adverse effects by the therapy (pain, redness, pigmentations). In the evaluation of digital photography, improvement was independently assessed by the author and another dermatologist, and expressed as a cumulative summary assessment. Patients were followed up for three and six months after the treatment, and evaluated on the basis of the scale given in the Annex. For a statistical analysis of data obtained during the survey a base in the statistical program SPSS for Windows 13,0 was created. During the computer analysis, statistical methodologies were used as follows: distribution of frequencies (absolute and relative representation) to present the categorical variables; descriptive methods (measures of central tendency - average, median, minimum, maximum values to present the quantitative variables; to test the significance of differences between the analyzed groups non-parametric (Chi-square test, Fisher exact test, Mann-Whitney U test), and parametric tests (t-test for independent samples, Analysis of Variance) were used depending on the nature of the data i.e. their distribution;as a level of significance or importance was taken value of p <0.05, and as a highly significant value of p <0.01. The results and conclusion: fractional CO2 laser used in treatment of patients with acne scars, is an effective and safe method that causes statistically significant better effect of the treatment, greater patients’ satisfaction, minimal side effects and statistically better response to the therapy, according to assessments by the patient and the therapist. In the treatment of skin rejuvenation, the laser treatment is effective and safe, causing statistically significant higher satisfaction in relation to the control group of patients. Satisfaction with the treatment in patients undergoing rejuvenation is greater than in any of the examined groups. Fractional carbon dioxide laser is safe to use in treatment of viral diseases of the skin and mucous membranes, condylomas and warts, without distinct side effects and discomfort in the treated patients. However, the effect of the therapy and patients’ satisfaction, and also evaluation by the doctors is statistically lower in relation to the control group of patients. In all three indicative subgroups of the laser examined group (acnes, rejuvenation, viral warts) there are no statistically significant mutual differences in relation to the laser treatment, i.e. it is equally efficient. The combined laser treatment using platelet-rich plasma versus laser monotherapy shows greater cumulative assessment of the effect of applied treatment, but without statistical significance, i.e. it is not significant. At the same time, the combined laser therapy with PRP is associated with greater patients’ satisfaction by the treatment and with significantly greater satisfaction with the appearance of pigmentation after the treatment versus laser monotherapy.
Efficiency of carbon dioxide fractional laser in skin resurfasing
Докторска дисертација одбранета во 2015 година на Медицинскиот факултет во Скопје.